Visualizing Dynamic Mechanical Actions with High Sensitivity and High Resolution by Near‐Distance Mechanoluminescence Imaging. Issue 36 (5th August 2022) - Zhuang, Yixi; Li, Xinya; Lin, Feiyan; Chen, Changjian; Wu, Zishuang; Luo, Hongde; Jin, Libo; Xie, Rong‐Jun
Abstract: Proportionally converting the applied mechanical energy into photons by individual mechanoluminescent (ML) micrometer‐sized particles opens a new way to develop intelligent electronic skins as it promises high‐resolution stress distribution visualization and fast response. However, a big challenge for ML sensing technology is its low sensitivity in detecting stress. In this work, a novel stress distribution sensor with the detection sensitivity enhanced by two orders of magnitude is developed by combining a proposed near‐distance ML imaging scheme with an improved mechano‐to‐photon convertor. The enhanced sensitivity is the main contributor to the realization of a maximum photon harvesting rate of ≈80% in the near‐distance ML imaging scheme. The developed near‐distance ML sensor shows a high sensitivity with a detection limit down to ≈kPa level, high spatial resolution of 254 dpi, and fast response with an interval of 3.3 ms, which allows for high‐resolution and real‐time visualization of complex mechanical actions such as irregular solid contacts or fluid impacts, and thus enables use in intelligent electronic skin, structural health monitoring, and human–computer interaction. Abstract : High‐sensitivity and high‐resolution visualization of dynamic mechanical action is achieved by a proposed near‐distance mechanoluminescence (ML) imaging scheme and an enhanced mechano‐to‐photon convertor. The developed portable ML stress sensor exhibits high sensitivity with a threshold of ≈kPa level, high spatial resolution with a pixel size ≈100 µm, and fast response of ≈3.3 ms.